Correction of Faradays law - Лёзов, П.П. (Radiotekhnika, 2012)
Faraday law of electromagnetic induction is considered and it is shown that the basis of the final integral expression of the electromotive force is a vector-scalar product of three quantities, namely, magnetic induction, motion speed of the conductor and its length. Only the lateral (transverse) component of the magnetic induction, the perimeter of the contour and the velocity of the magnet, is taken into account as applied to Faraday experiment according to Lorentz law. The basic method is the graphic study of the cylindrical magnet of the magnetic field structure and repetition of Faraday experiment with four different solenoids in turn.